About the impact of individually tailored plyometric training on the competitive performance of amateur boxers - Muntasir Ayman Anvar, Al-Shbul; Myasnikova, T.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the impact of individualised physical training using plyometric exercises on the competitive performance of amateur boxers. Methods and structure of the study. A 6-week plyometric programme was developed, taking into account the individual characteristics of athletes identified by their psychophysiological indicators. The experiment involved amateur boxers from Jordan (average age 23.2±2.9 years), who were divided into three groups depending on their ‘weak link’: speed (17 people), endurance (14 people) and power/coordination (20 people). Results and conclusions. The results showed that a plyometric programme tailored to specific physical deficiencies led to significant and targeted improvements in the boxers’ competitive performance. This confirms the importance of preliminary testing to identify deficiencies and optimise training in conditions of limited resources.